Limnology of Botos Lake, a tropical crater lake in Costa Rica - Umaña V., Gerardo (2001)
Botos Lake, located at the Poas Volcano complex (Costa Rica) was sampled eight times from 1994 to 1996 for physicochemical conditions of the water column and phytoplanktonic community composition. Depth was measured at fixed intervals in several transects across the lake to determine its main morphometric characteristics. The lake has an outlet to the north. It is located 2580 m above sea level and is shallow, with a mean depth of 1.8 m and a relative depth of 2.42 (surface area 10.33 ha, estimated volume 47.3 hm3). The lake showed an isothermal water column in all occasions, but it heats and cools completely according to weather fluctuations. Water transparency reached the bottom on most occasions (> 9 m). The results support the idea that the lake is polymictic and oligotrophic. The lake has at least 23 species of planktonic algae, but it was always dominated by dinoflagellates, especially Peridinium inconspicuum. The shore line is populated by a sparse population of Isoetes sp. and Eleocharis sp. mainly in the northern shore where the bottom has a gentle slope and the forest does not reach the shore.